Al-Uzmah al-Biṭrikiyah fī Riwāyati “Nisyān” Li Ahlām Mustagānemiy (Dirāsah Nisāiyah ‘alā Ḍaui Naẓariyah Julia Kresteva) - Husna wati Zahra; Arief Rahman Hakim (Journal of Arabic Literature (JaLi), 2021)
This research aims to find out the forms of the patriarchal crisis and the factors that lead to the emergence of the patriarchal problem represented in the novel "Nisyan" by Ahlam Mosteghanemi from the perspective of the feminist theory of Julia Kristeva. The research was qualitative and descriptive. The data sources used for this research are the primary data source in the form of the novel "Nisyan" by Ahlam Mosteghanemi. The secondary source is the supporting books and journals related to the research topic. The method of data collection is reading, translation and writing. The data analysis method uses simulated criticism, that is, by examining the data and then interpreting the narrative representations and facts in the community based on the perspective of Julia Kristeva and concluding. The results of this research are 1. They were classifying the forms of the patriarchal crisis on the body of a mother and an imaginary father. The forms of patriarchal problems categorized in the mother's body are stereotypes, marginalization, sexual harassment, and violence. The forms classified in an imaginary father are Cinderella complex, Oedipus complex, multiple burdens, and the stigma of divorce. 2. The factors that lead to the emergence of the patriarchal crisis are classified in the maternal's body and the imaginary father. Depending on the maternal's body, the patriarchal crisis arises from factors of abjection failure, virginity, reproductive impairment, and body image. Then from the imaginary father, the patriarchal crisis arises from the factors of fixation, lovesick, tomboy, and baby blues